ҲӘЗИРГИ ҚАРАҚАЛПАҚ ЛИРИКАСЫНДА ТҮН ХРОНОТОПЫНЫҢ БЕРИЛИЎ ӨЗГЕШЕЛИКЛЕРИ (И.Юсупов, Ш.Сейитов, С.Ибрагимов шығармалары мысалында) - Зинатдинова, Г.И. (FAN va JAMIYAT, 2023)
The article examines the characteristics of the expression of the night chronotope in the modern Karakalpak lyrics. Examples from the works of I. Yusupov, Sh. Seyitov, S. Ibragimov are given and widely interpreted.